Back Cover: Rapid, Isothermal DNA Self‐Replication Induced by a Destabilizing Lesion (Angew. Chem. Int. Ed. 40/2013). Issue 40 (20th August 2013) - Kausar, Abu; Mitran, Catherine J.; Li, Yimeng; Gibbs‐Davis, Julianne M.
<x xml:space="preserve">Abstract</x> Like clockwork, rapid isothermal self‐replication of oligonucleotides can be achieved using a cross‐catalytic strategy as reported by J. M. Gibbs‐Davis et al. in their Communication on page 10577 ff. The presence of both a destabilizing lesion in one of the replicating fragments and concentrated DNA polymerase results in high reaction rates and are key to multiple replication cycles (Photo by Dean Albrecht).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>